Interplay Between Diabetes, Obesity and Glioblastoma Multiforme, and the Role of Nanotechnology in Its Treatment - Sourav De; Sabyasachi Banerjee; Gourab Dey; Subhasis Banerjee; S.K. Ashok Kumar (Journal of Nanotheranostics)
A very aggressive and deadly brain cancer, glioblastoma multiforme (GBM) poses formidable obstacles to effective therapy. Despite advancements in conventional therapies like surgery, chemotherapy, and radiation therapy, the prognosis for GBM patients remains poor, with limited survival outcomes. Nanotechnology is gaining popularity as a promising platform for managing GBM, offering targeted drug delivery, improved therapeutic efficacy, and reduced systemic toxicity. This review offers a comprehensive analysis of the current therapeutic approach for GBM using nanotechnology-based interventions. This study explored various nanocarrier (NC) systems like polymeric nanoparticles, liposomes, dendrimers, polymeric micelles, and mesoporous silica nanoparticles for improved precision as well as efficacy in encapsulating and delivering therapeutic agents to GBM tumors. Methods for improving drug delivery into GBM cells are described in this study, including novel delivery modalities such as convection-enhanced delivery, intranasal administration, magnetic hyperthermia, peptide-guided nanoparticles, and immune liposomes. It also explores the influence of diabetes and obesity on GBM prognosis and survival rates, suggesting that managing glucose levels and using metformin may improve patient outcomes. The discussion focuses on the advancements in nanotechnology-enabled GBM therapy, highlighting the challenges and opportunities in implementing these promising technologies in clinical practice. The study highlights the potential of nanotechnology and metabolic modulation in transforming GBM treatment strategies. To further understand how these factors impact GBM patients and develop innovative nanotechnology-based treatments for GBM and diabetes mellitus, more study is necessary.